THE CONCEPTION OF TIME IN SHAKESPEARE’S SONNETS - Moreira, Lidia da Cruz Cordeiro (A Cor das Letras, 2017)
Time is the main theme in twenty-two of William Shakespeare’s 126 sonnets dedicated to the Fair Youth, although its presence can be felt throughout the entire sequence. This article will investigate how the bard’s concern with Time may have been influenced by the thought of his age, and will analyse some of these twenty-two sonnets in which Time is a main issue.